Migrant background and the impact of the COVID-19 pandemic on mental healthcare consultations among children and adolescents in Norway: a nationwide registry study - Ingeborg Hess Elgersma; Rannveig Kaldager Hart; Melanie Lindsay Straiton; Lars Johan Hauge; Anne Reneflot (BMC, 2023)
Abstract Background Despite concern about migrant children's mental health and their access to mental healthcare services during the COVID-19 pandemic, this topic has attracted little research attention. This study aimed to examine the impact of the COVID-19 pandemic on the use primary and specialist healthcare services for mental health problems among children and adolescents with migrant background. Methods Using event study models, we investigated the impact of lockdown and subsequent COVID-19 infection control measures on children's health service use for mental health problems according to migrant background. Drawing on reimbursement data from Norwegian public healthcare providers we observe consultations in a pre-pandemic (2017-2019) and pandemic cohort (2019-2021) in primary and specialised care. Results The pre-pandemic cohort included 77 324 migrants, 78 406 descendants of migrants and 746 917 non-migrants and the pandemic cohort included 76 830 migrants, 88 331 descendants and 732 609 non-migrants (age 6-19). The full cohorts were observed for mental healthcare use in primary care while a subsample (age 6-16) was observed for health care use in specialist care. Lockdown resulted in a dip in consultation volumes for mental disorders for all children, but this dip was relatively larger and more persistent for children with migrant background. After lockdown, consultation volumes rose more for non-migrant children than for children with migrant background. Consultations in primary healthcare peaked during January to April 2021 for non-migrants and descendants of migrants, but not for migrants (4%, 95% CI -4 to 11). In specialist care during the same period, consultations dropped by 11% for migrants (95% CI -21 to -1). By October 2021, all mental health consultations in specialist care were up with 8% for non-migrants (95% CI 0 to 15), and down with -18% for migrants and -2% for descendants (95% CIs -31 to -5 and -14 to 10). Migrant males experienced the largest reduction in consultations. Conclusions Changes in consultation volumes among children with migrant background after lockdown were not as pronounced as for non-migrants, and at times actually decreased. This suggests that an increase in barriers to care emerged during the pandemic for children with a migrant background.